The African swine fever virus isolate Belgium 2018/1 shows high virulence in European wild boar. Issue 4 (12th February 2020) - Pikalo, Jutta; Schoder, Marie‐Eve; Sehl, Julia; Breithaupt, Angele; Tignon, Maryléne; Cay, Ann Brigitte; Gager, Anna Maria; Fischer, Melina; Beer, Martin; Blome, Sandra
Abstract: African swine fever (ASF) is one of the most important and complex viral diseases in domestic pigs and wild boar. Over the last decade, the disease has spread to several European and Asian countries and is now one of the major threats to profitable pig production worldwide. One of the more recently affected western countries is Belgium. To date, only wild boar are affected in a rather defined area in the Luxembourg region close to France, Luxembourg and Germany. While detailed sequence analyses were recently performed, biological characterization was still pending. Here, we report on the experimental inoculation of four sub‐adult wild boar to further characterize the virus and its distribution in different tissues. After oronasal inoculation with the virus strain 'Belgium 2018/1', all animals developed an acute and severe disease course with typical pathomorphological and histopathological lesions. Organs and blood samples were positive in qPCR, haemadsorption test and antigen lateral flow devices (LFD). Virus and viral genome were also detected in genitals and accessory sex glands of two boars. There were no antibodies detectable in commercial antibody ELISAs, antibody LFDs and indirect immunoperoxidase tests. Thus, the genotype II ASF virus isolate 'Belgium 2018/1' showed a highly virulent phenotype in European wild boar similar to parental viruses like Armenia 2007 and other previously characterized ASFV strains. The study also provided a large set of well‐characterized sample materials for test validation and assay harmonization.